Research Trends in Ionic Liquids as Green and Low-Cost Solvents: Bibliometric Analysis from 2013 to 2023 - Andika Purnama Shidiq; Risti Ragadhita; Meli Fiandini; Asep Bayu Dani Nandiyanto (Indonesian Journal of Limnology, 2023)
Challenged by global awareness of environmental problems and demands of the industrial revolution, the Ionic Liquids (ILs) approach as a cheap and environmentally friendly solvent has been explored in various chemical reactions in many industrial fields. This article aims to perform bibliometric analysis of ILs by combining mapping analysis using Publish or Pheris and VOSviewer software and to pinpoint trends in scientific research. For this purpose, an exploratory study with a quantitative approach was developed based on secondary data from journals in google scholar, between 2013 and 2023. The keywords used in the data search are Ionic Liquid, low cost, and green solvent. The bibliometric indicator refers to 1,000 different relevant articles from 52 publishers with the largest number of articles produced by Elsevier, totaling 423 articles. The results showed that the peak of production occurred in 2014 and then decreased every year. The main reason for this increase is the need for cheap and environmentally friendly solvents to replace expensive and environmentally damaging conventional solvents, while the decline is due to the shift of interest into the field of applied chemistry. From the results of the Bibliometric analysis, there are 9 clusters with 126 related terms including low-cost, green solvent, application, study, and extraction. The most popular terms in 2022-2023 are related to fuel terms. This study shows the importance of bibliometric analysis in providing analytical data about what phenomena occur. This research is expected to help and become a reference for researchers in conducting and determining research themes to be taken.